The vocational turn of adult education in Denmark – an analysis of adult education policy from the late 1990s. Issue 3 (4th May 2019) - Rasmussen, Palle; Larson, Anne; Cort, Pia
ABSTRACT: Denmark has a strong and versatile tradition of adult education. Over a long historical period, adult education for public enlightenment and leisure, for continuing study and for vocational and professional competence have been developed, been made part of state policy and been used by citizens. But in recent years the public and political presence of Danish adult education has changed. While education policy issues generally abound in public and political debates, adult education is given much less attention than earlier. In this article, we trace the causes of this and conclude that it reflects a turn towards focusing on vocational types of adult education and a relocation of adult education policy to networks linking the state and the social partners. Drawing on theories of policy streams, policy networks and the competition state, we provide a historical analysis of Danish adult education reforms during the past two decades and document how the vocational turn has manifested itself.